DARI KAMPUS KE JALANAN: SUATU TINJAUAN ATAS GERAKAN MAHASISWA DI MALAYSIA - Mohammad Maiwan (Program Studi PPKn FIS UNJ & Asosiasi Profesi PPKn Indonesia, 2013)
Actually student movement in Malaysia have owned lenght history. Their movement have close related to development of politics. In the past, student movement emerge as part of the struggle to claim independence. But after independence, actively student activism emerge to response some various issues, about domestic or international problems. Their movement was beside pushed by idealism attitude and awareness of high politics, also influenced by turbulence of world politics. Tops of activism student movement in Malaysia taken place in year-end 1960s until early 1970s. Thereafter student movement lost ground. Existing political system solidy have limited various involvement of student in politics, so that cause they withdraw from various issue and problem outside campus.